Increasing rates of venous thromboembolism among hospitalised patients with inflammatory bowel disease: a nationwide analysis. Issue 7 (25th July 2022) - Faye, Adam S.; Lee, Kate E.; Dodson, John; Chodosh, Joshua; Hudesman, David; Remzi, Feza; Wright, Jason D.; Friedman, Alexander M.; Shaukat, Aasma; Wen, Timothy
Summary: Background: Venous thromboembolism (VTE) is a significant cause of morbidity and mortality among patients with inflammatory bowel disease (IBD). However, data on national trends remain limited. Aims: To assess national trends in VTE‐associated hospitalisations among patients with IBD as well as risk factors for, and mortality associated with, these events Methods: Using the U.S. Nationwide Inpatient Sample from 2000–2018, temporal trends in VTE were assessed using the National Cancer Institute's Joinpoint Regression Program with estimates presented as the average annual percent change (AAPC) with 95% confidence intervals (CIs). Results: Between 2000 and 2018, there were 4, 859, 728 hospitalisations among patients with IBD, with 128, 236 (2.6%) having a VTE, and 6352 associated deaths. The rate of VTE among hospitalised patients with IBD increased from 192 to 295 cases per 10, 000 hospitalisations (AAPC 2.4%, 95%CI 1.4%, 3.4%, p < 0.001), and remained significant when stratified by ulcerative colitis (UC) and Crohn's disease as well as by deep vein thrombosis and pulmonary embolism. On multivariable analysis, increasing age, male sex, UC (aOR: 1.30, 95%CI 1.26, 1.33), identifying as non‐Hispanic Black, and chronic corticosteroid use (aOR: 1.22, 95%CI 1.16, 1.29) were associated with an increased risk of a VTE‐associated hospitalisation. Conclusion: Rates of VTE‐associated hospitalisations are increasing among patients with IBD. Continued efforts need to be placed on education and risk reduction. Abstract : Increasing Rates of Venous Thromboembolism Among Hospitalized Patients with Inflammatory Bowel Disease.